Indirect speech acts and persuasive strategies of cultural narratives of Go’et in health promotion - Daar, Gabriel Fredi; Fithriyah Inda Nur Abida; Lisetyo Ariyanti; Rahayu Kuswardani (Journal of Applied Studies in Language, 2025)
Studies of cultural narratives as indirect speech acts and persuasive strategies in health promotion remain limited. This study aims to discover how "Go’et," a cultural narrative of Manggarai Community Indonesia, is used as an indirect speech act and persuasive strategy in health promotion. It is a qualitative study with a phenomenological approach. The study was conducted in the Rego dialect community, Manggarai, Indonesia. The study participants were chosen purposively based on predetermined criteria. The participants included healthcare providers, customary leaders, and community figures. Data from the study were collected using in-depth interviews, observation, documentation and Focus Group Discussion. The study indicated that the cultural narratives of Go’et in the Manggarai community in Indonesia are relevant to the context of health promotion. The cultural narratives are constructed in imperative sentences with the illocutionary power of advising, recommending and hoping. Using indirect speech acts through "Go’et" has become a persuasive strategy for shaping people's perceptions, beliefs and behavior.  Healthcare providers can adopt such expressions to positively influence patients' emotional states, enhancing their psychological readiness to recover or maintain good health. The study contributes to understanding how cultural narratives function as indirect speech acts in non-Western communities, particularly within the Manggarai context of Indonesia. By highlighting Go’et as a culturally embedded form of communication, the study expands the theoretical discourse on indirectness, politeness strategies, and persuasive communication in health promotion. Moreover, the study provides valuable insights into community-based health promotion strategies by emphasizing the compelling role of traditional discourse.